Abolition of mitochondrial substrate‐level phosphorylation by itaconic acid produced by LPS‐induced Irg1 expression in cells of murine macrophage lineage. Issue 1 (10th September 2015) - Németh, Beata; Doczi, Judit; Csete, Daniel; Kacso, Gergely; Ravasz, Dora; Adams, Daniel; Kiss, Gergely; Nagy, Adam M.; Horvath, Gergo; Tretter, Laszlo; Mócsai, Attila; Csépáinyi‐Kömi, Roland; et al.
ABSTRACT: Itaconate is a nonamino organic acid exhibiting antimicrobial effects. It has been recently identified in cells of macrophage lineage as a product of an enzyme encoded by immunoresponsive gene 1 ( Irg1 ), acting on the citric acid cycle intermediate cis‐aconitate. In mitochondria, itaconate can be converted by succinate‐coenzyme A (CoA) ligase to itaconyl‐CoA at the expense of ATP (or GTP), and is also a weak competitive inhibitor of complex II. Here, we investigated specific bioenergetic effects of increased itaconate production mediated by LPS‐induced stimulation of Irg1 in murine bone marrow‐derived macrophages (BMDM) and RAW‐264.7 cells. In rotenone‐treated macrophage cells, stimulation by LPS led to impairment in substrate‐level phosphorylation (SLP) of in situ mitochondria, deduced by a reversal in the directionality of the adenine nucleotide translocase operation. In RAW‐264.7 cells, the LPS‐induced impairment in SLP was reversed by short‐interfering RNA(siRNA)—but not scrambled siRNA—treatment directed against Irg1. LPS dose‐dependently inhibited oxygen consumption rates (61‐91%) and elevated glycolysis rates (>21%) in BMDM but not RAW‐264.7 cells, studied under various metabolic conditions. In isolated mouse liver mitochondria treated with rotenone, itaconate dose‐dependently (0.5‐2 mM) reversed the operation of adenine nucleotide translocase, implying impairment in SLP, an effect that was partially mimicked by malonate. However, malonate yielded greater ADP‐induced depolarizations (3‐19%) than itaconate. We postulate that itaconate abolishes SLP due to 1) a "CoA trap" in the form of itaconyl‐CoA that negatively affects the upstream supply of succinyl‐CoA from the α‐ketoglutarate dehydrogenase complex; 2) depletion of ATP (or GTP), which are required for the thioesterification by succinate‐CoA ligase; and 3) inhibition of complex II leading to a buildup of succinate which shifts succinate‐CoA ligase equilibrium toward ATP (or GTP) utilization. Our results support the notion that Irg1 ‐expressing cells of macrophage lineage lose the capacity of mitochondrial SLP for producing itaconate during mounting of an immune defense.—Németh, B., Doczi, J., Csete, D., Kacso, G., Ravasz, D., Adams, D., Kiss, G., Nagy, A. M., Horvath, G., Tretter, L., Mócsai, A., Csépányi‐Kömi, R., Iordanov, I., Adam‐Vizi, V., Chinopoulos, C. Abolition of mitochondrial substrate‐level phosphorylation by itaconic acid produced by LPS‐induced Irg1 expression in cells of murine macrophage lineage. FASEB J. 30, 286‐300 (2016). www.fasebj.org